2005
DOI: 10.1158/1535-7163.mct-04-0295
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative activity of angiotensin II receptor blocker through cross-talk between stromal and epithelial prostate cancer cells

Abstract: We showed previously that angiotensin II activated the proliferation of prostate cancer cells and that angiotensin II receptor blockers (ARB) could inhibit it. Here, we investigated whether angiotensin II exerts mitogenic effects on the cross-talk between stromal and cancer cells and whether an ARB can inhibit tumor growth through actions on stromal cells. Cell proliferation and interleukin-6 secretion of prostate stromal PrSC cells stimulated with angiotensin II, tumor necrosis factor-A, or epidermal growth f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
67
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 32 publications
6
67
1
2
Order By: Relevance
“…In PrSC, mRNA expressions of FGF-2 and FGF-7 were detected (data not shown). Previous report showed that responsiveness of E9 cells to FGF-2 and and IL-6 secretion from PrSC (15). It is highly important that naftopidil shows antiproliferative effects not only on cancer cells but also on stromal cells, and that stromal cell growth was inhibited by lower concentrations than that required to inhibit cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In PrSC, mRNA expressions of FGF-2 and FGF-7 were detected (data not shown). Previous report showed that responsiveness of E9 cells to FGF-2 and and IL-6 secretion from PrSC (15). It is highly important that naftopidil shows antiproliferative effects not only on cancer cells but also on stromal cells, and that stromal cell growth was inhibited by lower concentrations than that required to inhibit cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Olumi et al demonstrated stroma-induced malignant transformation, indicating that fibroblasts surrounding epithelia play an important role in PCa development (14). Other groups reported that coinoculation of PCa cells with fibroblasts increased tumorigenicity and implied the promotion of angiogenesis (11,15,16). Therefore, the inhibition of tumor-stroma interactions with addition of the suppression of cancer cell growth might lead to synergistic effects on tumor control.…”
Section: Introductionmentioning
confidence: 99%
“…We previously clarified that angiotensin II acted as a growth factor in prostate cancer and stromal cells (14,16). Interestingly, earlier investigators have reported that angiotensin II induced oxidative stress in vascular cells, for example, demonstrating that angiotensin II stimulated the production of ROS in endothelial cells by up-regulating the subunits of NADPH oxidases (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have reported that angiotensin II facilitates the secretion of some growth factors and cytokines from prostate stromal cells, resulting in cell proliferation of prostate cancer (16). Given that angiotensin II induces oxidative stress in vascular cells, it is very interesting to speculate that angiotensin II may function as an inducer of oxidative stress implicated in carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation